2021
DOI: 10.1073/pnas.2008880118
|View full text |Cite
|
Sign up to set email alerts
|

Three-step nucleation of metal–organic framework nanocrystals

Abstract: Metal–organic frameworks (MOFs) are crystalline nanoporous materials with great potential for a wide range of industrial applications. Understanding the nucleation and early growth stages of these materials from a solution is critical for their design and synthesis. Despite their importance, the pathways through which MOFs nucleate are largely unknown. Using a combination of in situ liquid-phase and cryogenic transmission electron microscopy, we show that zeolitic imidazolate framework-8 MOF nanocrystals nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
94
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 70 publications
2
94
0
2
Order By: Relevance
“…Such clusters are referred to as pre-nucleation clusters (PNCs), although their existence is open to debate 24 , 25 . The nucleation process believed to involve PNCs evolves in order of the phase separation, condensation, and ripening, and is often referred to as multistep nucleation in a broad sense 26 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Such clusters are referred to as pre-nucleation clusters (PNCs), although their existence is open to debate 24 , 25 . The nucleation process believed to involve PNCs evolves in order of the phase separation, condensation, and ripening, and is often referred to as multistep nucleation in a broad sense 26 29 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Some systems have also shown a distinct intermediate step in which the DLP condenses into an amorphous phase prior to crystallization. 4 These studies, among others, 18 suggest that the two-step mechanism via a DLP can readily be accessed in a wide range of solution-based systems, because, when taken to sufficiently high supersaturation, nearly all solutions will reach their limit of stability. 19 One aspect of these two-step pathways via a DLP that remains largely unexplored is that the stoichiometry of the intermediate phase is variable and ill-defined and must evolve to generate the final stable phase.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent work has also shown a distinct intermediate step involving the formation of an amorphous aggregate. 4 Here we report a novel four-step mechanism in the aqueous synthesis of sodium yttrium fluoride involving 1) the segregation of aqueous ions into a dense liquid phase, 2) the formation of an amorphous aggregate, 3) nucleation of a cubic YF 3 phase, and 4) subsequent solid-state diffusion of sodium and fluoride ions to form a final NaYF 4 phase. The final step involves a continuous, gradual change of the solid phase's chemical stoichiometry from YF 3 toward NaYF 4 .…”
mentioning
confidence: 99%
“… 5 , 6 However, recent research on zeolite and MOF crystallization has shown multiple deviations from classical crystallization theories. 7 , 8…”
Section: Introductionmentioning
confidence: 99%
“… 9 11 In fact, a three-step crystallization mechanism has been proposed recently for ZIF-8. 7 Nonclassical growth mechanisms have also been recently proposed as a deviation from the classical monomer-by-monomer based crystal growth, including for composite systems such as protein-MOF composites. 7 , 12 14 Nonclassical growth can occur because of the attachment of oligomers or amorphous clusters or through the oriented attachment of nanocrystals.…”
Section: Introductionmentioning
confidence: 99%